Tugas, Fungsi, dan Tujuan Filsafat Dakwah - Rohman (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
This research examines the urgency of the philosophy of da'wah in the modern context, focusing on its duties, functions, and objectives in the development of da'wah activities. Using a qualitative method with a library research approach, this research analyzes various literature sources including books, journals, articles, and relevant online sources. The results showed that the philosophy of da'wah has a vital role as a conceptual foundation and analytical tool in understanding and developing da'wah in the contemporary era. It performs its duties in formulating theological foundations, developing effective methods, and evaluating da'wah practices. Its functions include providing a conceptual framework, aligning da'wah with the social context, and developing dynamic methods. Its objectives not only focus on spiritual aspects, but also encompass broader social transformation, including the development of social awareness, the realization of justice, and the establishment of a sustainable Islamic civilization. This study concludes that the philosophy of da'wah is a crucial element in ensuring the relevance and effectiveness of da'wah amid the dynamics of modern society